2016
DOI: 10.1007/s10592-016-0910-x
|View full text |Cite
|
Sign up to set email alerts
|

Red foxes colonizing the tundra: genetic analysis as a tool for population management

Abstract: Climate change accelerates biodiversity alterations in northern ecosystems. A prevalent example is that tundra regions are invaded by boreal species. This impacts negatively on native species through competition, predation and transmission of zoonoses. Scandinavian red foxes (Vulpes vulpes) have emerged into the tundra and have altered the structure and function of the tundra community. For instance, they threaten persistence of the endangered Swedish Arctic fox (Vulpes lagopus). County board administrations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…The Fennoscandian red fox population is connected by high and asymmetric dispersal, but no major genetic temporal shift has been detected, which indicates that the ongoing northern population increase is a combined effect of in situ demographic growth and immigration (Norén et al 2015). Surrounding boreal areas thus function as sources that augment the alpine tundra population with colonizers from multiple directions (Norén et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The Fennoscandian red fox population is connected by high and asymmetric dispersal, but no major genetic temporal shift has been detected, which indicates that the ongoing northern population increase is a combined effect of in situ demographic growth and immigration (Norén et al 2015). Surrounding boreal areas thus function as sources that augment the alpine tundra population with colonizers from multiple directions (Norén et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…A genetic approach to the management of invasive species is gathering momentum. The information gleaned from this analysis of gene flow and population structure has broad implications for quarantine, trade and management of Bactrocera correcta 7 , Bemisia tabaci biotype B 8 , and Vulpes vulpes 9 . Coupled with ecological information on dispersal and/or colonization mechanisms and life-history characteristics, population genetics analyses provide a strong basis to formulate management strategies 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (Norén et al 2015, Norén et al 2017 revealed low levels of red fox population structure. We therefore estimated basic population genetic parameters within each country.…”
Section: Mitochondrial Data Analysismentioning
confidence: 85%
“…We assembled 259 red foxes, of which 79 originated from Sweden, 66 from Finland, 94 from Norway, 16 from Denmark, and 4 from the Kola Peninsula. These samples have previously been included in (Norén et al 2015, Norén et al 2017 or range-wide phylogeography (Statham et al 2014). Among these 259 samples, 72 sequences were collected by Statham et al (2014) and references therein.…”
Section: Samples and Dna Extractionmentioning
confidence: 99%
See 1 more Smart Citation